SISTEM TINGGI DALAM REALISASI KADASTER 3D DI INDONESIA: TANTANGAN, PERMASALAHAN DAN ALTERNATIF SOLUSI - Leni S Heliani; M. Ellya Putriningtias; Nurrohmat Widjajanti (BHUMI: Jurnal Agraria dan Pertanahan, 2013)
One important componentin the3Dcadastral system isthe definition of height component. The height of a cadastralobjectis the height above a certain height reference field. Based on theconceptandits use, there aremany height reference fields.Each reference field will have a certain effect on the type of height system and on the corresponding precision. Theabsoluteheightisdefinedin reference to thenationalheight reference, which provides certaintyandcleargeometricandtopologicalrelationsfor3Dcadastralobjects. However, the ideal nationalheight reference field,in this case precisegeoidmodels has not been definedfor thewhole of Indonesia.An alternativesolution to the problem uses a definition ofalocalgeoidmodel or the use ofa high-resolutionglobalgeoidmodel, the EGM2008. In the implementation, the precision level ofthe available geoid model and the required precision level of cadastral objects height become the basis for the selection of ageoid model. The use ofthe geoid modelasthe height reference has also an impact on theoptimalization/development of theapplication of BPNCORSstationsthatcan beusedas ahorizontal as well as a verticalreferencepointin3Dcadastralmapping.Keywords: 3D cadastre, cadastral mapping, geoid.